2015
DOI: 10.1002/srin.201500145
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Texture Evolution in Non‐oriented Electrical Steels Along Novel Strip Casting Route and Conventional Route

Abstract: In this article, evolution of microstructure and texture in non‐oriented electrical steels along novel strip casting route and conventional route are comparatively investigated in detail. It demonstrates the similar and important role of the microstructure and texture prior to cold rolling to finally obtain desirable recrystallization microstructure and texture in both routes. In both routes, a high intensity of cube‐fiber texture and a low intensity of γ‐fiber texture can be acquired in hot strips by optimizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…In this texture is feasible to observer that the grains have high stored energy, while the grains with the direction <110> parallel to the rolling direction belong to the -fiber (called as <110>//RD) contain a lower energy. It has been observed that as the amount of -fibre has an inverse relationship with the amount of -fibre [11][12][13]. Finally, finished product shows stronger marked component (554)2 2 5] on TD around -fibre grains [21], additionally, marked components in (554)225, in (221)1 1 0 deflected 25 o from component (111)1 1 0, and (332)1 1 3 deflected 30 o from component (111)//1 1 2], all components with rotations around 111//ND.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this texture is feasible to observer that the grains have high stored energy, while the grains with the direction <110> parallel to the rolling direction belong to the -fiber (called as <110>//RD) contain a lower energy. It has been observed that as the amount of -fibre has an inverse relationship with the amount of -fibre [11][12][13]. Finally, finished product shows stronger marked component (554)2 2 5] on TD around -fibre grains [21], additionally, marked components in (554)225, in (221)1 1 0 deflected 25 o from component (111)1 1 0, and (332)1 1 3 deflected 30 o from component (111)//1 1 2], all components with rotations around 111//ND.…”
Section: Resultsmentioning
confidence: 99%
“…The evolution of the microstructure and texture in low carbon steels processed by plastic deformation are produced by a variation in its energy stored during the deformation. In the case of highly deformed steels, stored energy is mainly concentrated as generation and interaction between dislocations [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Abovementioned applies too for continuous annealing process where both mechanical properties and microstructure are altered [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic yoke material for oriented silicon steel, relative permeability of µ 1 approximately 7000-10000. Choosing oriented silicon steel not only effectively increases the binding magnetic ability of magnetic yokes, but also has the fairly small reluctance, which has little effect on the reluctance measurement [13]. In Fig.…”
Section: Model Construction and Application A Model Constructionmentioning
confidence: 99%
“…The effects of the processing steps: hot rolling, hot band annealing before cold rolling (optional), cold rolling, and final annealing on the evolution of the magnetic texture have been widely studied . This includes also new technologies for hot band fabrication.…”
Section: Introductionmentioning
confidence: 99%